BUDAYA ORGANISASI DALAM PRESPEKTIF AL-QUR’AN DAN AL-HADIST - Fitri Wah Yuni; Suci Midsyahri Azizah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
Organizational culture is a set of philosophies, ideologies, norms that are owned by an organization which at the same time distinguishes it from other organizations. Faced with challenges that show that the organization has so far only been managed with mathematical approaches that are full of competitive nuances. In the midst of the problems faced, namely about what noble values ​​(core values) should not be conveyed in the practice of forming organizational culture so far. This article intends to know the concept of organizational culture in general, as well as to know the signs of the Qur'an and Hadith. The method used in writing this article is a descriptive qualitative method of library research type. The results of the study indicate that Islamically organizational culture is a gathering place for people who have ideas and thoughts that are in line, take the concepts and habits that have been embedded in the Islamic order as the basis for moving and effort in an effort to achieve organizational goals for the benefit and welfare of the organization. blessing of Allah SWT. The Islamic order that is taken as the organizational culture includes the concepts, models and values ​​contained in the organization